Diagnostic Accuracy and Clinical Outcomes in Acute Coronary Syndrome of OMI/NOMI VS STEMI/NSTEMI: a Systematic Review - Mamasta, Khairuman Fitrah Ananda; Sianturi, Agustina (Riviera Publishing, 2025)
Background: In the current STEMI-based model for diagnosing acute myocardial infarction (AMI), many patients classified as NSTEMI may actually have undetected acute coronary occlusion. As a result, these patients miss the opportunity for timely reperfusion therapy and experience worse outcomes than those with non-occlusive myocardial infarction (NOMI). To address this issue, a revised paradigm has been proposed that differentiates occlusion MI (OMI) from non-occlusion MI (NOMI). Methods: This systematic review included eight studies published between 2020 and 2024. All studies evaluated patients with acute coronary syndrome (ACS), comparing diagnostic performance and clinical outcomes between the traditional STEMI/NSTEMI paradigm and the emerging OMI/NOMI paradigm. The studies employed various designs, including retrospective cohorts, case-control analyses, and cross-sectional studies, to assess diagnostic accuracy and treatment outcomes. Results: Evaluation of ECG diagnostic performance showed that OMI-specific ECG patterns had significantly higher sensitivity (86%) and diagnostic accuracy (89%) compared to standard STEMI criteria (41% sensitivity, 77% accuracy). Several studies reported substantial delays in recognition and management of OMI when relying solely on STEMI criteria. Evidence consistently demonstrated that patients with OMI, especially those misclassified as NSTEMI, had outcomes equal to or worse than those with STEMI. Conclusion: The OMI paradigm highlights major quality gaps in the emergency care of ACS patients. Transitioning from the traditional STEMI/NSTEMI model to OMI/NOMI classification can improve diagnostic precision, identify care delays, and guide quality improvement interventions to optimize patient outcomes.